Identifikasi dan Kelimpahan Plankton pada Budidaya Ikan Air Tawar Ramah Lingkungan - Sri Oetami Madyowati, Maria Agustini (AGROKNOW, 2014)
Abstract. Sampling was carried out at 11 noon with overcast weather conditions, while the physical parameters temperature 27o C with a brightness of 47.83 cm. Water depth of 9.95 m with a length of the pool, the pool width 5.3 m with a height of 0.5 m of water. Light green color of pool water showed dominance Chlorophyta. Chemical parameters of 2.13 ppm of dissolved oxygen, carbon dioxide 14, 96 ppm, with a pool in the range of neutral pH is 7, obtained Gloeotrichia echinulata plankton species that are most at 42.85% at the level of abundance of each species relatife at all sampling stations, with the amount of plankton in the pond at 11.80. 109 cells. Physical parameters in this study also contributed to the presence of plankton present in the water, too, especially for the process of photosynthesis and respiration of aquatic organisms.Kata kunci: identifikasi plankton, kelimpahan plankton, ramah lingkungan.